Performance of shallow borehole of spiral-tube ground heat exchanger / Jalaluddin, Rustan Tarakka and Akio Miyara - Jalaluddin,, Rustan Tarakka; Akio, Miyara (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
The use of geothermal energy has been recognized as a possible solution for reducing emissions. This energy source is a renewable and green energy sources with wide applications such as for space air conditioning and hot water supply. A ground heat exchanger (GHE) can be applied in the space air conditioning system for exchanging heat with the ground. This study present an investigation of thermal performance of shallow spiral-tube GHE buried in the 5 m depth. The performance of this GHE is investigated by numerical method using CFD code. The performance of the spiral-tube GHE is 46.9 Watt per meter borehole depth in laminar flow and 64.6 Watt per meter borehole depth in turbulent flow. Comparison between the spiral-tube and the conventional U-tube GHEs shows the possibility to reduce borehole depth and installation cost. Using the spiral-tube GHE can reduce the borehole about a half compared with using the conventional U-tube GHE. Shallow spiral-tube GHEs can be arranged in series and parallel configurations to meet the needs in the application.